The Lived Experience of PLWHA and Partner’s Responses toward the Fulfillment of Sexual Needs - Supartha, I Gede Nyoman Ardi; Waluyo, Agung; Kariasa, I Made (Department of Nursing, Faculty of Medicine, Diponegoro University, 2017)
Background: Every single person including people living with HIV/AIDS (PLWHA) have five basic needs; one of which is a physiological sexual need. Unfortunately, PLWHA face many difficulties in fulfilling their sexual needs due to the stigma and fear of infecting their partner.Purpose: The purpose of this study was to explore the lived experience of PLWHA and partner’s responses toward the fulfillment of sexual needs.Methods: This study was a qualitative descriptive phenomenological research, which collected data through in-depth interviews from fourteen PLWHA in Paramacitta Spirit Foundation, Denpasar. The participants were recruited through snowball sampling, informed and gave consent for their voluntary participation. The data were analyzed using Colaizzi’s phenomenological method.Results: The study revealed five themes describing the sexual experiences of PLWHA, including: (1) the fulfillment of sexual need of PLWHA, (2) the roles of partner for PLWHA, (3) various perceived stimuli which could increase the sexual desire, (4) the perceived factors which could incapacitate the ability and quality of sexual desire, and (5) the efforts to increase sexual capability and quality. Conclusion: Sex was an important need for PLWHA to meet. Despite having a virus, after undergoing anti-retroviral (ARV) treatment, PLWHA felt healthier, and thus they could meet their sexual need like a normal person in general.